From History to Architecture: Speelwijk Fort: A Symbol of Dutch Dominance Over Banten - Khabiba, Reisya Aulia; Azzahra, Vilza; Aimah, Nafatul; Hakim, Lukman; Fajrio, Reika; Hamid, Abd Rahman; Setiawan, Agus Mahfudin (Swarnadwipa, 2025)
This article examines the historical establishment of Fort Speelwijk as a symbol of Dutch and Banten Sultanate relations. The study aims to explore cultural acculturation and shifts in governance arising from their interaction. This research uses the historical method, including heuristics, source criticism, interpretation, and historiography. Built in Dutch architectural style by Hendrik Lucaz Cardeel and named after Governor-General Cornelis Janszoon Speelman, the fort functioned as the VOC's representative office in Banten. The findings reveal cultural acculturation in construction techniques, including brick and coral stone reinforced with lime, reflecting the local concept of “Gawe Kuta Baluwarti Bata Kalawan Kawis.” Economically, the VOC’s tax imposition led to rising commodity prices, burdening locals and weakening the Sultanate’s economic sovereignty. Additionally, the study explores local myths surrounding the fort, such as the story of Catharina Maria Van Doorn. After its 1994 restoration, Fort Speelwijk emerged as a prominent historical and educational tourism site.